Genome-wide association study identifies novel susceptibility loci for KIT D816V positive mastocytosis - Galata, Gabriella; García-Montero, Andrés C.; Kristensen, Thomas; Dawoud, Ahmed A. Z.; Muñoz-Gonźalez, Javier Ignacio; Meggendorfer, Manja; Guglielmelli, Paola; Hoade, Yvette; Alvarez-Twose, Ivan; Gieger, Christian; Strauch, Konstantin; Ferrucci, Luigi; et al. (The American journal of human genetics, 2021)
Mastocytosis is a rare myeloid neoplasm characterized by uncontrolled expansion of mast cells, driven in >80% of affected individuals by acquisition of the KIT D816V mutation. To explore the hypothesis that inherited variation predisposes to mastocytosis, we performed a two-stage genome-wide association study, analyzing 1,035 individuals with KIT D816V positive disease and 17,960 healthy control individuals from five European populations. After quality control, we tested 592,007 SNPs at stage 1 and 75 SNPs at stage 2 for association by using logistic regression and performed a fixed effects meta-analysis to combine evidence across the two stages. From the meta-analysis, we identified three intergenic SNPs associated with mastocytosis that achieved genome-wide significance without heterogeneity between cohorts: rs4616402 (pmeta = 1.37 × 10−15, OR = 1.52), rs4662380 (pmeta = 2.11 × 10−12, OR = 1.46), and rs13077541 (pmeta = 2.10 × 10−9, OR = 1.33). Expression quantitative trait analyses demonstrated that rs4616402 is associated with the expression of CEBPA (peQTL = 2.3 × 10−14), a gene encoding a transcription factor known to play a critical role in myelopoiesis. The role of the other two SNPs is less clear: rs4662380 is associated with expression of the long non-coding RNA gene TEX41 (peQTL = 2.55 × 10−11), whereas rs13077541 is associated with the expression of TBL1XR1, which encodes transducin (β)-like 1 X-linked receptor 1 (peQTL = 5.70 × 10−8). In individuals with available data and non-advanced disease, rs4616402 was associated with age at presentation (p = 0.009; beta = 4.41; n = 422). Additional focused analysis identified suggestive associations between mastocytosis and genetic variation at TERT, TPSAB1/TPSB2, and IL13. These findings demonstrate that multiple germline variants predispose to KIT D816V positive mastocytosis and provide novel avenues for functional investigation.